KONSEP UTANG DALAM HUKUM KEPAILITAN DIKAITKAN DENGAN PEMBUKTIAN SEDERHANA (STUDI PUTUSAN NO: 04/PDT.SUS.PAILIT/2015/PN.NIAGA.JKT.PST) - Robert Robert; Sunarmi Sunarmi; Dedi Harianto; Keizerina Devi Azwar (Universitas Sumatera Utara, 2016)
ABSTRACT Verification process plays a vital role to resolve a case. in the verification of bankruptcy cases which is carried out with a simple verification. This simple verification in practice often causes a problem because because there are not any lucid parameters related to it in the UUKPKPU (Law on Bankruptcy and Suspension of Debt Payment Obligation) This simple verification frequently disregards the aim and philosophy of the Bankruptcy Law because it can facilitate a debtor’s bankruptcy that is still solvent or be taken advantage by a bad debtor to apply for a fictive bankruptcy. The wide debt concept in the bankruptcy law tends to be unable to be simply verified, so the insolvency test can be used as a verified method alternative o apply for a bankruptcy statement so that the bankruptcy application can meet the objective and philosophy of the bankruptcy itself. Judges are not supposed to be rigid or positivistic in examining and adjudicating the case they face because they will tend to fail to notice the stakeholders’ sense of justice. Keyword: Bankruptcy, Simple Verification, Debt Concept.